RANCANG BANGUN DAN SIMULASI PROTEUS SISTEM LAMPU OTOMATIS MENGGUNAKAN SENSOR LDR DAN RANGKAIAN KOMPARATOR LM324 - Erika; Sya’diah, Halimatus; Desta Azzahra, Lathifah; Amri, Fauzan; Kurnianingtyas, Rahajeng (JURNAL REKAYASA ENERGI, 2025)
This project was developed to create an automatic system that can control a lamp based on the surrounding light conditions. The system uses an LDR (Light Dependent Resistor) sensor to detect light intensity and an LM324 IC as a comparator to determine when the lamp should turn on or off. When the ambient light decreases (such as during nighttime), the resistance of the LDR changes and sends a signal to the LM324 circuit. The main purpose of this system is to enable the lamp to automatically turn on when it gets dark and turn off when it becomes bright again, without the need for manual switching. In this way, the system helps to save electrical energy and improve lighting efficiency, especially in areas that are often forgotten to be turned off, such as porches or garden lights. Based on the testing results, the system functions properly and responds quickly to changes in light. The circuit is also stable and easy to build, as it uses simple and commonly available components. Overall, this system is suitable for various lighting automation purposes in residential areas as well as public spaces.